Ampas Penyulingan Nilam Sebagai Bahan Bakar Alternatif Pada Proses Produksi Minyak Nilam - Sugiarto, Sugiarto; Sulistyo, Erwin (Jurnal Rekayasa Mesin, 2010)
Remaining organic waste product of nilam oil distillation is a potential biomass as a fuel substitute for firewood. Utilization of waste distillation during refining is considered not yet optimal. Whereas by utilizing distillation waste will be obtained by the double advantage is decreasing the cost of production like reduction of the cost of purchasing firewood, waking environment from illegal logging and encroachment uncontrolled firewood and maintaining forest conservation. This research was conducted by varying waste of nilam distillation mixed fuel with firewood with a variation of 0%, 25%, 50%, 75% and 100% waste compared to firewood. Distillation capacity of each process is 60 kg of raw materials that have been chopped dried nilam. Dependent variables are sought in the form of heating value, temperature data in space heating, steam temperature and volume of nilam oil is produced for each variation of fuel weight fraction of waste nilam. The result is a solid fuel heating value increases with increasing weight fraction of waste nilam compared to the firewood. Zones heating temperatures and steam temperature fluctuated or not stable for all variations of fuel weight fraction of waste nilam. Steam temperature below 100 Â° C which indicates the water content in the steam is still high. Time required for each distillation process with a capacity of 60 kg is still relatively long time is 5 to 6 hours. Volume nilam oil products tend to increase with increasing weight fraction of fuel from the dregs of nilam. Keywords : Waste distillation of nilam, alternative fuel, nilam oil